Rurality from the perspective of its inhabitants: Analyzing participant responses to in-depth questionnaires, photographs and reflections from an ethnographic study in Southern Ecuador - Emilia Alonso-Marks; Iván Salazar-Tornez (Revista Iberoamericana de Estudios de Desarrollo)
As part of an outgoing ethnographic study we examined the narratives, photographs and re- flections produced by participants from four rural communities within the Gonzanamá district, Loja province, southern Ecuador on the advantages and disadvantages of rural living. In this study, it is analyzed how these rural communities have created a dissident voice from the power relationships established by society, the government and the scientific community. Results have revealed how this three-part process was a powerful tool to give a voice to those who do not have one, to claim their rural spaces that define who they are as a community, and to state how to live true to their cultural heritage. In addition, these results have confirmed the contribution that qualitative studies make in the advancement of any type of quantitative study, especially in the area of international development.